The potential use of biomonitoring urban and sub-urban habitat quality based on leaf characteristics of sweet potato (Ipomoea batatas L.) - Ostrea, James Lloyd M. (2012)
This study aimed to assess the potential of leaf characteristics of sweet potato (Ipomoea batatas L.) as active bioindicator of urban habitat quality specifically to point out difference in habitat of urban and sub-urban areas. The study area was Tacloban City, Philippines. Three sampling locations in urban and sub-urban land use classes were selected. Stem cuttings planted were introduced to these sites for a period of one and a half months. Stomatal density, stomatal pore surface, stomatal resistance, shoot biomass, and specific leaf area from leaves of the stem cuttings were determined. Results showed that stomatal density was significantly higher in urban sites by 33% and 40% in the abaxial and adaxial sides respectively. Stomatal pore surface in the urban sites was significantly lower compared to sub-urban sites by -42% and -46% in the abaxial and adaxial leaf surfaces respectively. Abaxial stomatal resistance was significantly higher in urban sites due to reduction in stomatal pore surface. However, shoot biomass was not significantly different between urban and sub-urban sites and specific leaf area was significantly higher in sub-urban sites. Shading and microclimatic conditions may have accounted for these results. Based on the results, stomatal density and stomatal pore surface have promising potential as bioindicator of urban habitat quality.